ความอยู่รอดของเศรษฐกิจชุมชนภายใต้กระแสโลกาภิวัฒน์: กรณีศึกษากลุ่มใบตองคลองกระจง อำเภอสวรรคโลก จังหวัดสุโขทัย - อนุรักษ์ นรษี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study of Survival of Community Economy in Globalization: A Case Study of Baitong KlongKrajong Group, Sawankhaloke District, Sukhothai Province aims to study the general conditions of Baitong KlongKrajong Group’s members and also their group establishment. The main focus of this research is to study their systems of organization, activities management as well as problems and obstacles concerning the effects from Globalization. The research is a qualitative study in which the tools are questionnaires and interviews that were given to 70 people including the members of Baitong KlongKrajong Group as well as the farmers who grow banana leaves.